HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN STRES PADA REMAJA - Raudatul Jannah, Giva; Netrawati, Netrawati (Penerbit Lafadz Jaya, 2025)
This research is motivated by the phenomenon that shows symptoms of stress in adolescents, such as the inability of students to control emotions, irritability, anxiety, difficulty concentrating, difficulty getting along with peer groups and decreased social skills. One factor that influences stress is peer social support. This study aims to determine the relationship between peer social support and stress in adolescents. This study uses a quantitative method with a descriptive correlational research type. The population in this study were students of grades XI and XI at SMA Negeri 2 Batang Anai registered in the 2025/2026 academic year, with a sample of 228 students using a simple random sampling technique. The results of the study show that peer social support is generally in the fairly high category and stress in adolescents is generally in the fairly high category. The results of the product moment correlation test obtained rxy = -0.300 indicating a negative relationship with the level of the relationship being in the weak category.